2020
DOI: 10.3390/cancers12123521
|View full text |Cite
|
Sign up to set email alerts
|

SNP-SNP Interaction in Genes Encoding PD-1/PD-L1 Axis as a Potential Risk Factor for Clear Cell Renal Cell Carcinoma

Abstract: PD-1/PD-L1 axis plays an important role in maintaining homeostasis and prevention from autoimmunity; however, in the tumor microenvironment, PD-1/PD-L1 interaction is responsible for the evasion of immune surveillance by tumor cells. We therefore hypothesized that single nucleotide polymorphisms (SNPs) in genes encoding PD-1 and PD-L1 molecules are associated with the development and outcome of renal cell carcinoma (RCC). Here we genotyped nine polymorphisms: five of PDCD1: rs36084323G>A, rs11568821G>A, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 30 publications
0
17
0
Order By: Relevance
“…In this study, we analyzed the potential of three PD-1 SNPs as a predictive biomarker of nivolumab therapeutic outcome in patients with mRCC, because PD-1 is the primary target of this anti-PD-1 antibody [ 29 ]. PD-1, which is broadly expressed in multiple cell types, including T cells, B cells, dendritic cells, and macrophages, plays a role in down-regulating T-cell responses, leading to immune suppression.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we analyzed the potential of three PD-1 SNPs as a predictive biomarker of nivolumab therapeutic outcome in patients with mRCC, because PD-1 is the primary target of this anti-PD-1 antibody [ 29 ]. PD-1, which is broadly expressed in multiple cell types, including T cells, B cells, dendritic cells, and macrophages, plays a role in down-regulating T-cell responses, leading to immune suppression.…”
Section: Discussionmentioning
confidence: 99%
“…13 In this sense, numerous studies have demonstrated the role of specific genes in the development of different types of cancer. [14][15][16][17][18][19] The genetic atlas of cancer is a priority for cell and molecular biology with a view to discovering the different signaling pathways involved, and identifying new targets for the development of antitumor diagnostics and drugs.…”
Section: Cancer Incidence: Factors Involved In Its Origin and Develop...mentioning
confidence: 99%
“…Similarly, PD-1 rs11568821 synergy with CTLA-4 49AG:CT60 A:A haplotype has been associated with an increased risk of primary biliary cancer (PBC)[ 146 ]. Interactions between PD-L1 rs10815225 and PD-1 rs7421861 polymorphisms were also associated with the development and outcome of ccRCC[ 147 ]. No such observation has been reported so far for HCC, although the interaction between PD-L1 rs4143815 and PD-1 rs11568821 variants was found to be important in the liver transplantation setting.…”
Section: Pd-1/pd-l1 Genetic Variationsmentioning
confidence: 99%